Effect of the implementation of a technological resource on the teaching process in Accredited High-Quality Programs (2020)
The importance of this article lies in the need to train teachers in the process of incorporating digital resources into the teaching strategies developed in their chairs. A quantitative approach is adopted, for which a sample of 300 informants enrolled in three academic programmes in different faculties and which is recognised as being of high quality was formed. The results show malfunctions that need to be corrected to ensure their effectiveness and massive use in the institution.